Cumulative incidence of chronic pain after visiting a Dutch emergency department with acute pain - S. Mol; A. V. Brown; T. M. Kuijper; M. G. Bouwhuis; B. de Groot; A. J. Out; M. G. Ibelings; J. S. H.A. Koopman (BMC Anesthesiology)
Abstract Background Chronic pain is a substantial problem in modern healthcare resulting in health care overutilization. The cumulative incidence of developing chronic pain after visiting the emergency department with acute pain has been determined for specific patient groups only. If the cumulative incidence of chronic pain in emergency department patients with acute pain is high, more proactive measures are justified to limit development of chronic pain. The primary objective was to study the cumulative incidence of chronic pain in patients visiting Dutch emergency departments with acute pain. In addition, we compared the Health-Related Quality of Life (HRQOL) and pain related interference with work. Methods In this prospective multicenter cohort study data was collected from adult patients visiting the emergency department with acute pain. Chronic pain was defined by means of a numeric rating scale (NRS) of ≥ 1 measured 90 days after the initial visit. HRQOL was measured with European Quality of Life (EQ-5D-5 L) and Short Form (SF-36) questionnaires. Results 1906 patients were included of which 825 had complete data. Of these, 559 patients (67.8%; 95%CI: 64.5 − 70.9%) scored an NRS ≥ 1 after 90 days. Incidence with completed analyses (with imputed data) was similar. Patients with chronic pain reported a significantly lower HRQOL; EQ-5D-5 L index (median 0.82 vs. 1.00) and significantly more pain related hindrance (median 1.00 vs. 0.00). Conclusions 67.8% of the responders scored NRS ≥ 1 90 days after ED-visit with acute pain. Regardless of the used definition, chronic pain is associated with a lower HRQOL and more pain related hindrance.